Testing the efficiency market hypothesis for the colombian stock market (2014)
One of the basic assumptions of asset pricing models (CAPM and APT) is the efficiency of markets. This paper seeks to prove this requirement in its weak form, both for the General Index of the Stock Exchange of Colombia and for the Colombian market´s most representative assets. To this end, different statistical methods are implemented to show that stock patterns do not follow a normal distribution pattern. Additionally, when testing the Colombian efficiency market through a series of runs, BDS, LB and Bartlett test, there is no evidence of randomness in the main financial assets except Ecopetrol. Moreover, in the specific case of IGBC there is an improvement in market efficiency from 2008 to 2010, period that coincides with the onset of the global economic crisis.